2020
DOI: 10.1111/jfpp.14867
|View full text |Cite
|
Sign up to set email alerts
|

Adding value and innovation in dairy SMEs: From butter to probiotic butter and buttermilk

Abstract: Functional foods have a common feature of providing some functional advantage to consumers, being normally associated with food innovation (Tapsell, 2008). Their functionality may be associated to specific nutrients such as vitamins, minerals, fiber, prebiotics, or probiotics, but it is expected that they can deliver additional benefits over and above their basic nutritional value. Nowadays, there has been an increased interest in the development of new functional foods as a result of the increased awareness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…The lactic microbiota in sweet butter result from adventitious contamination and not from the intentional addition of microorganisms. The observed acidity values are higher than those reported by Ferreira et al for sweet and fermented butters containing probiotics [16]. The color parameters of all butters presented significant differences (p < 0.05) regarding lightness (L*), as well as regarding parameters a* (red-green axis) and b* (blue-yellow axis) (Table 2).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The lactic microbiota in sweet butter result from adventitious contamination and not from the intentional addition of microorganisms. The observed acidity values are higher than those reported by Ferreira et al for sweet and fermented butters containing probiotics [16]. The color parameters of all butters presented significant differences (p < 0.05) regarding lightness (L*), as well as regarding parameters a* (red-green axis) and b* (blue-yellow axis) (Table 2).…”
Section: Resultsmentioning
confidence: 59%
“…Usually, cream undergoes fermentation with mesophilic lactic acid bacteria, namely Lactococcus lactis ssp. dyacetilactis and/or Leuconostoc citrovorum (commonly referred to as an aromatic starter) [16]. Although the use of probiotic bacteria in cream has received little attention, some authors report their use, and their results will be compared to ours.…”
Section: Introductionmentioning
confidence: 98%
“…Many previous studies have attempted to incorporate probiotic organisms into dairy matrices directly. However, this resulted in interaction with the product, further impacting its organoleptic properties and a decline in probiotics viability over the storage period [ 6 , 7 , 8 ]. Out of all the strategies, encapsulation is perhaps the most effective technique for protecting the probiotics and retaining their bioactivity and viability [ 1 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the growing number of health-conscious consumers, functional foods that provide health benefits beyond basic nutrition have received particular attention [ 1 ]. Their functionalities may be associated with specific nutrients, such as vitamins, minerals, fiber, prebiotics, or probiotics, but they can deliver additional benefits above their basic nutritional values [ 2 ]. One key research area for the future functional food market is the development of probiotic food formulations, recognized as a major class of health-promoting foods that contain live microorganisms that, when administered in adequate amounts, confer health benefits on the host [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cream is the main raw material in the production of butter, the properties of which reflect the quality of the butter. Although the fermentation of cream with appropriate starter cultures of LAB is a well-known practice that implicates physicochemical and sensory properties of butter, and strongly influences its nutritional composition, textural properties, and shelf life, the use of LAB demonstrating probiotic properties in butter has been seldom reported in the literature [ 2 ]. Nevertheless, there are a few studies that have shown the abilities of probiotic bacteria to survive in butter at sufficient amounts to maintain probiotic effects, e.g., Bifidobacterium bifidum [ 7 ] and Lactobacillus acidophilus [ 6 ].…”
Section: Introductionmentioning
confidence: 99%